Peran Guru Agama Buddha Dalam Penguatan Pendidikan Karakter di SMPS Kasih Maitreya - Budi Yanto; Hosan Hosan; Sonika Sonika (Jurnal Maitreyawira, 2025)
This study aims to describe the role of Buddhist teachers and the implementation of strengthening character education at SMPS Kasih Maitreya Selatpanjang by using descriptive qualitative methods, data collection techniques with interviews, observations, questionnaires, and documentation. Character education is education that develops cultural values ​​and character in students so that it becomes the basis for them to think, behave, act in developing themselves as individuals, members of society, and citizens. The values ​​of strengthening character education that become dominant in this study include honest, disciplined, orderly, clean, creative, obedient, polite and caring, while the less dominant characters include respect, neatness. The results of the study show that first; The role of Buddhist teachers in strengthening character education at SMPS Kasih Maitreya Selatpanjang has been well implemented, as evidenced by the results of the percentage of questionnaires, observations, and interviews with principals and teachers of 84%. Second, the implementation of strengthening character education for students of SMPS Kasih Maitreya Selatpanjang has reached 53%, which the principal and teachers say has not been optimal in strengthening character in schools, so there needs to be improvements such as the habituation of school culture aspects of 5S (smiles, greetings, greetings, politeness, and kindness). polite), 3D (self-discipline, time discipline, and regulatory discipline), 3 Love (love heart, loving smile, and loving behavior), so that the character becomes a habit at school and outside of school.